A systematic review on CFST members under impulsive loading. (October 2022) - Dabbagh, Noaman Mohammed Ridha; Wan Badaruzzaman, Wan Hamidon; Al Zand, Ahmed W.; Kazemzadeh Azad, Sina; Uy, Brian; Azmi, Mohd Reza; Alatshan, Faesal
Abstract: Concrete-filled steel tubes (CFST) have been increasingly used in the construction industry due to their favourable structural performance. With the increase of accidental events in the past two decades, researchers paid more attention to the response of CFST members under impulsive (lateral impact/blast) loading. Research projects conducted aim to better understand the structural performance of CFST members through experimental, numerical, and analytical approaches. This paper aims to systematically characterise the state-of-the-art research on the structural behaviour of CFST subjected to lateral impulsive loading. The reviewed studies include circular and rectangular/square cross-sections, conventional members and those strengthened with fibre reinforced polymer (FRP). Members with normal strength concrete (NSC), high strength concrete (HSC), as well as ultra-high-strength concrete (UHSC) infill are all included. Following the literature review, the current research trends are identified, and potential future research directions are discussed based on the identified knowledge gaps. A consensus of the results shows that CFST members have superior resistance to impulsive loading compared to their hollow counterparts and reinforced concrete (RC) members. Highlights: Behaviour of CFST under impact and blast loading is reviewed. A systematic literature review approach is adopted. Lateral impact loading (low, high velocity) and blast loading (near, far range) are covered. CFST members strengthened with FRP are included. CFSTs with normal, high, and ultrahigh strength concrete infill are discussed.